Theory and method in higher education research - Huisman, Jeroen; Tight, Malcolm (Theory and method in higher education research ;, 2022)
Higher education research is a developing field internationally, which is attracting more and more researchers from a great variety of disciplinary backgrounds within and beyond higher education institutions. As such, it is an arena within which a wide range of theories, methods and methodologies is being applied. This volume of Theory and Method in Higher Education Research explores several timely topics including transnational approaches to higher education policy, universities contributions to society, data collection in higher education, virtual and blended research, and more. Including contributors from Australia, Iran, Denmark, Belgium, Germany, and the UK, the chapter authors present international perspectives on the application and development of theory and methodology in researching higher education.